Analisis Stakeholders Dalam Pengembangan Kawasan Strategis Pariwisata Kabupaten Wonosobo - Masrurun, Zam Zam; Nastiti, Dyah Meutia (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Stakeholders are one of the essential elements in maintaining competitiveness in efforts to manage tourism destinations. They are the main factor in the dynamics and development of the current tourism market. This study aimed to identify, classify, and describe the relationship between the stakeholders involved in the development of the Tourism Strategic Area in Wonosobo Regency. Data and information through field observations, in-depth interviews, and literature studies. The analysis technique in this study used a stakeholder mapping method approach. The sample in this study was forty-eight stakeholders determined based on the purposive sampling technique. The study result is an indication that twenty-eight stakeholders had a high interest in the development of the area. There were three key players or stakeholders with the most crucial roles and involvement in the area, i.e., two stakeholders in subject groups, five stakeholders in the context setters, and eighteen others in crowd groups. In addition, the research revealed five model schemes and relationships between stakeholders from government, private, and community groups. The success of the development of the Tourism Strategic Area in Wonosobo Regency determines the effectiveness and collaboration between the stakeholders. So, therefore, it would require commitment and synergy between institutions in conducting communication, coordination, and cooperation between agencies/institutions